Evaluation of Image Detection and Description Algorithms for Application in Monocular Slam - Urrea-Onate, E (IGI Global, 2017)
The results of new experiments on the detection and description of images for an EKF-SLAM monocular application are employed in order to obtain a dispersed set of features without related data association problems. By means of different detectors/descriptors, the number of features observed and the ability to observe the same feature in various captures is evaluated. To this end, a monocular vision system independent of the EKF-SLAM system is designed and implemented using the MatLab software. This new system allows for-in addition to image capture-the detection and description of features as well as the association of data between images, thus serving as a priori information to avoid incorrect associations between the obtained features and the map of an EKF-SLAM system. Additionally, it enables the evaluation and comparison of the precision, consistency and convergence of various algorithms. © 2017 IGI Global. All rights reserved.